Concepções e práticas de organização curricular dos professores do 1º ciclo de formação de uma escola da Rede Municipal de Educação de Cuiabá - MT - Rodrigues, Marilce da Costa Campos (2005)
The object of this study is to organize the Teachers Practical Curricular of the Primary School in Basic Education "Jesus Criança" situated in Cuiabá - MT, with the objective of understanding the process of practical curricular organization in pedagogical of these professors involved in this research. The research has a methodological support and uses as instrument of collections of data and subjects: the comment, the register of dialogued commentary, the interview and the documentary analysis. The orientation of the construction of the study object if gave from the questions: Which practical conceptions and of curricular organization guide the teaching action in 1º formation cycle? That modality of curricular organization is assumed by the practical school in curricular of the professors of 1º the cycle of formation? These questions had helped the understanding of this curricular organization in the spaces consisting of the moments of planning and the teaching action in classroom. The inquiry has its theoretical supports especially, in the following authors: Beane (1997); Freire (1987); Lopes (1999); Macedo and Lopes (2002); Sacristán and Gómez (1989); Sacristán (2000) and others. The collected and analyzed data give to know an approach at school, of a conception of curricular organization, that flexibly with trends: however more intense to the resume to discipline and however more intense to the integrated resume. The forms of curricular organization coexist in practical of the professors of 1º the cycle of formation in the searched school, being predominant disciplining, resume organized in a matrix to discipline are not impediment to the curricular integration.